Management of Pine Forests for Selected Wildlife in Florida - Wayne R. Marion; George W. Tanner; Holly K. Ober; Matthew Werner (EDIS)
As the total number of forested acres in Florida goes down, it becomes more important that land being managed for timber production also be able to sustain healthy wildlife populations. This 9-page fact sheet shows how timber and wildlife management can be successfully combined. Written by Wayne R. Marion, George W. Tanner, Holly K. Ober, and Matthew Werner, and published by the UF Department of Wildlife Ecology and Conservation, August 2011.